Real‐time detection of BDS orbit manoeuvres based on the combination of GPS and BDS observations. Issue 10 (1st October 2020) - Tu, Rui; Zhang, Rui; Liu, Zhanke; Fan, Lihong; Han, Junqiang; Zhang, Pengfei; Hong, Ju; Liu, Jinhai; Lu, Xiaochun
Abstract : The construction of the third generation of the Chinese BeiDou navigation satellite system (BDS), which provides global positioning, navigation, and timing (PNT) services, will be completed in 2020. As BDS satellites contain the geostationary orbit (GEO), inclined geosynchronous (IGSO), and medium earth orbit (MEO), orbital manoeuvres occur more frequently. Thus, orbit manoeuvre detection is important for continuous and reliable PNT services. A BDS orbit manoeuvre detection method based on the combination of global positioning system (GPS) and BDS observations is proposed in this study. The standard deviations of the observation residuals of the epoch‐differenced velocity estimation of the single BDS system and combined GPS + BDS system were compared to determine the beginning and end of the orbit manoeuvre. The results show that the orbital manoeuvre leads to a position, velocity, and receiver clock error bias of approximately tens to hundreds of metres, several centimetres per second, and tens to hundreds of metres, respectively. Based on the proposed method, the start and end times can be detected in real time and the usable observation time can be extended by >157 min.